The Influence of Audit Opinions and Audit Findings on the Level of Regional Government Corruption in Indonesia - Maulana Yusuf Ibrahim; Khomsiyah Khomsiyah (Citakonsultindo, 2024)
This research is motivated by the increasing trend of corruption cases and the potential for greater financial losses to the state. Data from the Indonesian Corruption Watch (ICW) in 2022 indicates that local government employees are the primary perpetrators of corruption. This study aims to analyze the influence of audit opinions and audit findings on the level of corruption in local governments in Indonesia. The data utilized includes the BPK RI Semester Examination Results Summary (IHPS) and Court Decision data from the Supreme Court Directory. Using multiple linear regression, the study examines the relationship between the independent variables (audit opinion and audit findings) and the dependent variable (level of corruption). The results indicate that audit opinions significantly influence local government corruption levels, with better audit opinions correlating with lower corruption levels. Conversely, audit findings do not significantly impact the level of corruption in local governments. The research suggests that improving the audit system and enhancing the quality of audit opinions can contribute to reducing corruption levels in local governments in Indonesia.